2018
DOI: 10.30684/etj.36.6a.1
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Site Selection for Groundwater wells using Integration between GIS and Hydrogeophysical Data

Abstract: This paper aim to select the best site to drill a groundwater wells by using of Geographic Information System (GIS) as a tool for decision-making. The study conducted in Fadak farm in Bahr Al-Najaf which is located west and southwest of Najaf city, and extends more than (40 km) away from it, to drill a new wells for irrigations usages. The optimal location selected depending on the available hydrogeophysical data includes resistivity, depth, thickness and transmissivity of aquifer. The weighted factor maps gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…Generally, the multi-criteria decision problems include a set of a potential decision alternative that is evaluated based on specific criteria [30]. Over the last decade, many studies have used the MCE in the GIS environment for different purposes e.g., [31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the multi-criteria decision problems include a set of a potential decision alternative that is evaluated based on specific criteria [30]. Over the last decade, many studies have used the MCE in the GIS environment for different purposes e.g., [31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, various studies utilized MCDA for groundwater suitability analysis with successful results. For example, Aziz et al [25] selected the best site to drill groundwater wells in the Fadak farm, South Iraq for irrigations purposes. The optimal location was selected depending on the hydrogeophysical data including resistivity, depth, thickness, and transmissivity of the aquifer.…”
Section: Suitability Mapmentioning
confidence: 99%
“…Therefore, GIS-based MCDA technique that efficiently combines multiple hydrological data to produce a reliable decision model is an effective tool to enhance the suitability analysis in an area of interest. Several researchers have used remote sensing and GIS-based MCDA in groundwater studies with effective results [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its low cost, easy to apply, and fast to get a result, it is correlated with the other methods. Besides, providing primary information and proposing the best suitable region for drilling low-cost wells (Ahmed et al 2012;Abdulrazzaq et al 2019), VES has demonstrated to be valuable in groundwater study; this technique has been extensively used in groundwater exploration to determine the depth to the water table, aquifer geometry, and groundwater feature by analyzing measured apparent resistivity field data (Aziz et al 2018). In designing suitable groundwater management schemes in any geological environment, whose properties (physical and chemical) and spatial circulation institute the purpose of all hydro-geological and hydro-geophysical investigations (Abdulrazzaq 2011), the ecology of the subsurface resources is of importance.…”
Section: Introductionmentioning
confidence: 99%